Reform of the organization a salary in healthcare the Republic of Kazakhstan - Есимжанова, С. (Journal of Economic Research & Business Administration, 2017)
This article addresses issues associated with wage organization of healthcare worker of the Republic of Kazakhstan. The process of establishing health workers’ current tariff rates, salaries, bonuses, wage supplements, surcharges and other incentive payments was analyzed. It contains statistics data of wage in healthcare in comparison with other areas of economic activity. On the basis of established practice problems in this area were identified, that is low level of workers payment and poor development of the system of collective bargaining regulation of wages payment size applied to private healthcare organizations. It was found that the current system of payment in the public sector under consideration is almost identical to the principles of the organization of wages in other sectors of economic activity, financed from the state budget. According to the results of the study there are specific proposals for improvement in wage organizing in healthcare organizations for various forms of ownership at the present stage of development of economy of the Republic of Kazakhstan.